Modelling the gas-liquid flow in an ironmaking blast furnace. (1st January 2004) - Yu, A.B.; Wang, G.X.; Chew, S.J.; Zulli, P.
A mathematical model is presented to describe the discrete flow of liquid within and below the blast furnace cohesive zone. The model is developed based on a force balance approach to describe the liquid flow and a stochastic treatment to take into account the complex packing structure. The interaction between gas and liquid flows has been included in the governing equations, so that the localised liquid flow in a packed bed can be modelled with or without gas flow. The validity is demonstrated by comparing model predictions and measurements obtained under different gas and/or liquid flow conditions. Application of the model to blast furnace is discussed with reference to the interaction between gas and liquid phases and the effect of cohesive zone shape.